Adorable interactions: investigating the influence of AI voice assistant cuteness on consumer usage intentions - Yu, Xintao; Liu, Xiaochen; Xu, Zhen (Frontiers in Communication, 2024)
In an era where user experience reigns supreme, an unexpected element is subtly influencing our interactions with technology-"Cuteness." However, when discussing the design of digital products such as AIVAs, is cuteness merely a matter of appearance? This paper aims to unveil the complex psychological mechanisms and their impact on usage intention hidden behind the seemingly harmless allure of cuteness. Through an experimental study involving 284 participants and utilizing a moderated serial mediation model via PLS-SEM, this research reveals how aesthetic design differences influence usage intentions. The findings disclose three key insights: (1) A positive relationship between cuteness and usage intention is confirmed; (2) Social presence, performance expectancy and customer value act as serial mediations between cuteness and usage intention; (3) Perceived risk moderates the impact of cuteness on usage intentions by influencing social presence, performance expectancy, hedonic value and functional value. This contributes theoretical insights and practical guidance for the sustainable development and success of AIVAs.